1994
DOI: 10.1002/ajmg.1320490209
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral femoral hypoplasia associated with Rokitansky sequence: Another example of a mesodermal malformation spectrum?

Abstract: We report on a woman with bilateral femoral hypoplasia and Rokitansky sequence, malformations that up to now had not been described together. There are no other cases in the family, and no history of prenatal teratogen exposure. This case may be part of a mesodermal malformation spectrum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Other mesodermal structures, especially skeletal structures, seem to be also susceptible to developmental disturbances during this time 3 . There are various reports in the literature concerning the association of MRKH sequence and skeletal anomalies 4,5 . Recently, MRKH syndrome associated with thrombocytopenia‐absent radius syndrome has been described, further substantiating a link between the development of the skeletal and genital system 2 .…”
Section: Discussionmentioning
confidence: 91%
“…Other mesodermal structures, especially skeletal structures, seem to be also susceptible to developmental disturbances during this time 3 . There are various reports in the literature concerning the association of MRKH sequence and skeletal anomalies 4,5 . Recently, MRKH syndrome associated with thrombocytopenia‐absent radius syndrome has been described, further substantiating a link between the development of the skeletal and genital system 2 .…”
Section: Discussionmentioning
confidence: 91%
“…In an analysis of 574 case reports, Griffin and associates found that 12% of the Mayer -Rokitansky patients exhibited skeletal anomalies (Stephens et al 1996). Bau et al (1994) reported a female with Rokitansky syndrome associated with bilateral femoral hypoplasia and normal kidneys. Strubbe et al (1994) studied the urographic, sonographic and laparoscopic findings of 100 women with MRKH syndrome and suggested that two separate subgroups existed -the typical group which included those with an isolated form of congenital agenesis of the vagina and uterus and the atypical group which included those with obligatory characteristic finding of agenesis of the vagina and uterus in addition to extra-genital features including asymmetrical muscle buds and renal anomalies, amongst others.…”
Section: Discussionmentioning
confidence: 98%